The Influence of Religiosity and Customer Perception on Interest in Savings - Yunita Maulidiyah Faha; Masruchin Masruchin; Fitri Nur Latifah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Sharia Banking is an institution that functions to collect and channel public funds effectively and efficiently which is useful for improving economic and national quality. The problem that occurs is that the development of Islamic banks is growing, the competition between banks, both conventional banks and Islamic banks, will be increasingly tight. Therefore, the need for efforts from banks to attract customers' savings. The main success of the services provided by banks is not only from internal factors but also external factors. Internal factors include the amount of funds owned by banks and credit, while external factors include the level of trust and bank image. This research aims to analyze and prove that religiosity and perception affect the interest in saving in Islamic banks. The approach used is a quantitative approach using primary and secondary data. The population of this research is the customers of BSI KCP Mojokerto Bangsal as many as 700 customers and the sample obtained is 161 respondents. This sampling uses the Cochran table formula with the respondents' criteria, namely BSI KCP Bangsal customers and aged 17-50 years. Analysis of the data used is SPSS 22 software. This research is survey research conducted through data collection using multiple regression analysis techniques. The results show that the religiosity variable has an influence on interest in saving in Islamic banks with a value of 32.860 > 1.960, while the perception variable has an influence on interest in saving in Islamic banks because the value is 21.954 > 1.960. From these results, Islamic banks have opportunities to improve performance and events that are useful for explaining Islamic bank products to customers.